2016
DOI: 10.1111/ijcp.12867
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undiagnosed hyperglycaemia in patients presenting to the Department of Emergency Medicine with no known history of diabetes

Abstract: Over 2% of patients who presented to the DEM were hyperglycaemic, without a prior diagnosis of diabetes. A small per cent was recommended to have outpatient follow-up. This represents a missed opportunity for earlier diagnosis of diabetes and emphasised the need for raising medical staff awareness concerning abnormal blood glucose and its implication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…For example, in all three patients diagnosed with diabetes during their admission, this was in their discharge summaries, along with newly prescribed medications. Ideally, a request for follow-up should be found in the discharge referral of patients diagnosed with diabetes or those found to have blood glucose or HbA1c results suggestive of diabetes, and absence of such records may compromise the ability for treatment and prevention of complications [18,29,30], which may result in a higher risk of re-admission [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in all three patients diagnosed with diabetes during their admission, this was in their discharge summaries, along with newly prescribed medications. Ideally, a request for follow-up should be found in the discharge referral of patients diagnosed with diabetes or those found to have blood glucose or HbA1c results suggestive of diabetes, and absence of such records may compromise the ability for treatment and prevention of complications [18,29,30], which may result in a higher risk of re-admission [31].…”
Section: Discussionmentioning
confidence: 99%
“…The ED also provides medical care to people with little or no access to screening and preventive interventions; therefore, initiating a screening intervention in the ED may improve the health of this vulnerable population. The ED of Campbelltown hospital of SWS serves approximately 283,743 residents across the district (ABS Census 2016) [17] and during a visit to the ED, blood glucose levels are also regularly tested particularly in high-risk individuals, making the department a potentially valuable location to conduct opportunistic screening for diabetes [12,[18][19][20]. Given the large number of presentations at the ED, missed opportunities for diabetes screening could be common [21] and patients who are newly diagnosed with diabetes from the screening test may not have been closely monitored [22].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical investigation of inpatient hyperglycaemia is infrequent, 38,39 despite high prevalence 40 and physician support for increased intervention. 41 There appears to be a lack of clinical research in this area, with only a small number of studies identified in this review.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Prior research demonstrates that ED diabetes surveillance protocols using only random, blood glucose measurements have been successful. [6][7][8][9][10] Patient characteristics, such as demographics, 11 body mass index (BMI), family history, comorbidities, and laboratory measures of impaired glucose tolerance, hemoglobin A1c (HbA1c), cholesterol, and triglycerides, can be used to refine a screening decision for diabetes. Confirmatory testing such as fasting plasma glucose, oral glucose tolerance testing, or HbA1C should be considered for definitive diabetes diagnosis.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%